Open-source implementation of polarisation-resolved single-shot differential phase contrast microscopy (pDPC) on a modular openFrame-based microscope - Huihui Liu; Sunil Kumar; Edwin Garcia; William Flanagan; Jonathan Lightley; Christopher Dunsby; Paul M.W. French (HardwareX)
We recently demonstrated polarisation differential phase contrast microscopy (pDPC) as a robust, low-cost single-shot implementation of (semi)quantitative phase imaging based on differential phase microscopy. pDPC utilises a polarisation-sensitive camera to simultaneously acquire four obliquely transilluminated images from which phase images mapping spatial variation of optical path difference can be calculated. pDPC microscopy can be implemented on existing or bespoke microscopes and can utilise radiation at a wide range of visible to near infrared wavelengths and so is straightforward to integrate with fluorescence microscopy. Here we present a low-cost open-source pDPC module that is designed for use with the modular open-source microscope stand “openFrame”. With improved hardware and software, this new pDPC implementation provides a real-time readout of phase across a field of view that facilitates optimisation of system alignment. We also provide protocols for background subtraction and correction of crosstalk.